TEMPORAL DIFFERENCES IN THE REALISATION OF SPECIFIC COMBAT TECHNIQUES RELATIVE TO SPATIAL ABILITY - Gužvica, Milan; Paspalj, Darko; Vrućinić, Žana; Vulin, Lazar (NBP. Nauka, bezbednosti, policija, 2020)
In this paper, the time of performing 15 motor tests that consisted of different modalities of punches and kicks was measured on a sample of 44 subjects (24 men and 20 women), as well as the speed of performing cognitive test S1, from a battery of KOG3 tests. The results were obtained using appropriate statistical procedures, and they indicate that women in most cases, from both items, achieved better results compared to men when it comes to a simple motor reaction, while men achieved better results with a complex motor reaction. The obtained concurrence of motor tests with test S1 for men ranges from a complete absence of concurrence for five techniques derived from the left guard to high concurrence for three techniques derived from the right guard. When it comes to women, the absence of any concurrence was registered in two techniques from one and the other guard, and high concurrence for five techniques from the right guard. It is believed that the obtained results can be useful for further teaching process in Special Physical Education.